2022
DOI: 10.3390/ma15217750
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Tribological Performance of TiAlNbN Hard Coatings by Adding AlCrN

Abstract: In tribological applications, the degradation of alloy nitride coatings is an issue of increasing concern. The drawbacks of monolayer hard coatings can be overcome using a multilayer coating system. In this study, single-layer TiAlNbN and multilayer TiAlNbN/AlCrN coatings with AlCrN layer addition into TiAlNbN were prepared by cathodic arc evaporation (CAE). The multilayer TiAlNbN/AlCrN showed B1 NaCl structure, and the columnar structure continued from the bottom interlayer of CrN to the top multilayers witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…*PMPivkin@gmail.com; phone +7 499 972-94-56; https://www.researchgate.net/profile/Petr-Pivkin Also, Ti-TiN-(Ti,Al,Cr)N composite coatings improve tribological properties, increase wear resistance and heat resistance during high-speed processing [12][13]. Nanocoatings [14][15][16][17], due to their small coating thickness and high hardness, contribute to increased durability, while during their scanning their reflectivity can change, which can cause a decrease in the area of focal areas, which leads to a decrease in the step when forming images during scanning [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…*PMPivkin@gmail.com; phone +7 499 972-94-56; https://www.researchgate.net/profile/Petr-Pivkin Also, Ti-TiN-(Ti,Al,Cr)N composite coatings improve tribological properties, increase wear resistance and heat resistance during high-speed processing [12][13]. Nanocoatings [14][15][16][17], due to their small coating thickness and high hardness, contribute to increased durability, while during their scanning their reflectivity can change, which can cause a decrease in the area of focal areas, which leads to a decrease in the step when forming images during scanning [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…From the above literature review, high-entropy alloy nitride coatings show promising potential as protective coatings for cutting tools, forming dies, and other high-temperature applications due to their extraordinarily high hardness, mechanical properties, and hightemperature tribological behaviors. Since the AlCrN coatings exhibit very high hardness and good wear resistance [27,28], adding AlCr alloying elements into coatings was explored [29][30][31]. Kang and coworkers [29] studied the influence of AlCr contents on the microstructure, mechanical properties, electrical resistivity, and corrosion behavior of (AlCr)x(HfMoNbZr)1-x thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Tang et al discussed the effect of AlCr content on the mechanical properties of AlTiCrN coatings grown with HiPIMS and noted that the hardness decreased with increasing AlCr content [30]. Chang and Huang also reported that the hardness and tribological properties of TiAlNbN coatings can be improved by adding an AlCrN multilayer [31]. Therefore, the effect of adding Nb, Si, and Ti elements into the AlCrN coating in terms of the microstructure, mechanical properties, and corrosion resistance changes in AlCrNbSiTiN coatings is worthy of study.…”
Section: Introductionmentioning
confidence: 99%